Utilization of Teacher-Made Learning Activity Sheets as a Tool in Improving Learners’ Numeracy Skills: An Action Research - Padernos, Jessy Lou F (Future Science / FSH-PH Publications, 2024)
Developing learners’ numeracy skills has been a pressing issue in the field of education, as it is one of the battlecries of the agency along with literacy. Studies revealed that addressing these learning gaps varies widely across schools, classrooms, and learners. Moreover, students learn better through the activities that their teachers provide to them. Thus, under the Mathematics Foundation Fluency Program, a numeracy intervention program of Langkaan II National High School, teacher-made learning activity sheets were used as learning materials of the learners under numeracy intervention. The objective of this study is to determine the effectiveness of utilizing teacher-made learning activity sheets in improving the numeracy skills of the learners particularly in Langkaan II National High School. The findings of the study will serve as a help in improving the numeracy intervention program of the school. The results revealed that there was a marked improvement in the numeracy skills of the learners as manifested in the improved scores of the learners during the post-test. Moreover, no non-numerates were reported during the end-of-the-school year numeracy assessment. Thus, using the teacher-made learning activity sheets were found to be an effective tool in improving the numeracy skills of the learners including number sense, number operations, measurement, geometry, patterns and algebra, and statistics and probability. It helped the students to cope up certain topic/lessons in basic mathematics that develops their numeracy skills. These materials can contribute to a more comprehensive program to improve the numeracy skills of the learners. Further studies may also be conducted as to other aspects relevant to the implementation of the whole program. Validation or modification of these learning materials may also be conducted for further enhancement.